2008
DOI: 10.1007/s00542-008-0639-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polymer inks for drop-on-demand printing systems

Abstract: This paper presents a detailed study on the properties of different polymer inks based on poly(3,4eth-ylenedioxythiophene)/polystyrenesulfonate regarding their processability in an experimental piezo driven drop-ondemand (DoD) micro-feeding system. Based on the rheological properties of the used inks and the mechanical properties of the printing system characteristic values are derived which allow to predict the processability of polymer inks in a given printing system. Beside the printability the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Images from Drop Watcher were analyzed using ImageJ™ software to determine drop diameter and velocity. The inverse Ohnesorge number, Z −1 , and energy number, En, which describe drop stability and jettability [16], respectively, were calculated based on the drop and nozzle geometry and the ink rheology:…”
Section: Ink Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Images from Drop Watcher were analyzed using ImageJ™ software to determine drop diameter and velocity. The inverse Ohnesorge number, Z −1 , and energy number, En, which describe drop stability and jettability [16], respectively, were calculated based on the drop and nozzle geometry and the ink rheology:…”
Section: Ink Formulationmentioning
confidence: 99%
“…Meixner et al [16] sug-gested a value of En < 1 to avoid droplet splashing and spraying, and 1 < Z −1 < 10 to form stable drops. The inks with the best jetting performance and appropriate viscosity were treated with carbon nanotube (CNT) solution [7].…”
Section: Ink Formulationmentioning
confidence: 99%
“…Li et al (2008) investigated the printing frequency effects, and reported that distorted meniscus and liquid thread were broken into several satellites at higher frequency. Meixner et al (2008) studied the properties of different polymer inks in piezo DoD micro-feeding system. Based on the rheological properties of the used inks and the mechanical properties of the printing system, characteristic values are derived and utilized to predict the process capability of polymer inks.…”
Section: Introductionmentioning
confidence: 99%
“…Since droplet formation process requires highly loaded particulate suspension, and operating parameters vary with materials properties (van den Berg et al 2007;De Gans et al 2005), viscosity and surface tension of this suspension are identified as key parameters (Derby and Reis 2003). To explore the relationship between viscosity and driving voltage in dispensing, Meixner et al (2008) compared polymer inks with variable viscosity and surface tension based on PEDOT:PSS. The results showed that for the same surface tension, the higher viscosity liquid required larger voltage to produce droplets.…”
Section: Introductionmentioning
confidence: 99%